2004
DOI: 10.1590/s1806-83242004000100008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soft tissues on mandibular gray scale levels

Abstract: The purpose of this study was to analyze the gray levels, expressed in pixels, of the mandibular retromolar region, with regard to the influence of muscular and fat soft tissues near this region. Fifteen dry mandibles were X-rayed with the presence of soft tissue simulators. The radiographs were digitized and evaluated by Digora® software. A one cm thick layer of wax was used as a simulator of the muscular soft tissue. Animal fat samples of different thicknesses - 0.5, 1.0, 1.5 and 2.0 cm - were used as a simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
0
12
0
7
Order By: Relevance
“…These results are in accordance with a previous study. 17 Furthermore, Wx, Wd and Bt showed an increased grey-level gain according to the increase in thickness.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These results are in accordance with a previous study. 17 Furthermore, Wx, Wd and Bt showed an increased grey-level gain according to the increase in thickness.…”
Section: Discussionmentioning
confidence: 93%
“…3 As radiographic tissue density is derived from this attenuation coefficient degree, quantification of the density becomes more accurate when the influence of soft-tissue simulator materials is taken into consideration. 17 According to Souza et al, 17 different materials with the same thickness showed different optical densities in the mandibular bone area, using digitized film-based radiographic images. However, the differences with the methodology used in our study make it difficult to compare the findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of such studies it has been considered important to simulate the soft tissues (cheek) by using a material interposed between the X-ray beam and the teeth/bone, because soft tissues change the absorption and increase scatter radiation, and may influence the contrast and density of the film (and thereby diagnostic accuracy). In fact, Souza et al 1 showed that animal fat samples of different thicknesses used as a soft-tissue simulator adjacent to the mandibular retromolar region influenced the resulting grey level values in digitized intraoral radiographs.…”
Section: Introductionmentioning
confidence: 99%